Pengaruh Kompetensi Profesional Guru Dan Sarana Pembelajaran Terhadap Prestasi Akademik Peserta Didik Di SMA Negeri 1 Banjar - Syarifah Syarifah (Jurnal Pendidikan Indonesia (JOUPI), 2023)
The background of this research is the lack of optimal teacher professional competence in improving the academic achievement of students at SMA Negeri 1 Banjar. The aims of this study were to: 1) Know the influence of the professional competence of teachers at SMA Negeri 1 Banjar on the academic achievement of students. 2) To determine the effect of learning facilities at SMA Negeri 1 Banjar on the academic achievement of students. 3) To determine the effect of teacher professional competence and learning facilities on the academic achievement of students of SMA Negeri 1 Banjar. The research method used is descriptive method with a quantitative approach. The data collection technique was carried out by distributing questionnaires with a total of 69 respondents. Statistical data processing using SPSS 21.0. The results of the study show that 1) Professional Competency of Teachers at SMA Negeri 1 Banjar in general is always on the answer with quite high criteria. However, there are indicators that need to be improved, namely the selection of learning models and methods, as well as creating learning media that can attract students' attention to improve their learning at school. The results of the hypothesis test show that the teacher's professional competence has an effect of 40.7% on students' academic achievement while 59.3% is affected by other factors. 2) The learning facilities in SMA Negeri 1 Banjar are generally in the frequent answers with quite high criteria. There are several indicators that must be improved, including the use of student worksheets in learning activities and the use of ICT-based learning media. The results of the hypothesis test show that learning media have an effect of 44% on students' academic achievement while 56% is influenced by other factors. 3) The academic achievements of students at SMA Negeri 1 Banjar are generally in the frequent answers with quite high criteria. However, there are indicators that need to be improved, namely evaluating learning outcomes, creating ideas, seeking information, and the ability to perform skills in learning. The test results on the relationship between teacher professional competence and learning facilities and students' academic achievement are included in the strong correlation category, then there is a positive influence of teacher professional competence and learning facilities on students' academic achievement.